Introduction of the ART approach in Egypt: Intentions, clinical effects and perceived barriers. A cohort study. (May 2013) - Farag, Abeer; van der Sanden, Wil J. M.; Mulder, Jan; Creugers, Nico H. J.; Frencken, Jo E.
Abstract: Aim. To evaluate the effect of the introduction of ART in Upper-Egypt and assess the participating General Dental Practitioners' (GDPs) opinions, intentions, expectations and experiences regarding barriers related to using ART. Methods. Thirty-five GDPs were selected and trained on ART for 5 days. Knowledge assessments were done immediately before and after the training, using a questionnaire. Regular evaluation and assessment data were collected after 6 and 12 months, through questionnaires with closed and open-ended questions. Clinical data in government and private clinics were collected, using clinical record-forms. GDPs' opinions, intentions, expectations and experiences regarding barriers related to ART were assessed, through questionnaires, at the start and after 1 year. The control group comprised 35 other GPDs. Results. At the start, the most GDPs were intended to make ART restorations. After 1 year 65% and 97% actually made ART restorations in their government and private clinics, respectively. The barriers faced by the GDPs to making ART restorations in the government clinics were mainly unavailability of suitable restoration material and of hand instruments. After 1 year post-training, ART restorations constituted 41% of the total plastic restorations made. Finally, the majority of GDPs believe that ART is suitable for use in their government and private practices. Conclusion. All participating GDPs intended to introduce ART in their government and private clinics. They successfully introduced this technique in their private clinics but, owing to the unavailability of suitable instruments and restoration materials, failed to do so in the government clinics. They liked the simplicity of the technique.